2021
DOI: 10.1093/gji/ggab096
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory acoustic emission activity of hydraulic fracture in granite with various viscous fluids revealed by deep learning technique

Abstract: Summary To investigate the influence of fluid viscosity on the fracturing process, we conducted hydraulic fracturing experiments on Kurokami-jima granite specimens with resins of various viscosities. We monitored the acoustic emission (AE) activity during fracturing and estimated the moment tensor (MT) solutions for 54 727 AE events using a deep learning technique. We observed the breakdown at 14–22 MPa of borehole pressure, which was dependent on the viscosity, as well as two preparatory phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…They showed that a CNN model was capable of locating microseismic events and reconstructing the velocity model simultaneously in real-time from seismic waveforms. Tanaka et al [49] employed a deep learning model to perform moment tensor inversion of acoustic emissions during a hydraulic fracturing experiment of granite rock and obtained 54,727 solutions.…”
Section: Deep Learningmentioning
confidence: 99%
“…They showed that a CNN model was capable of locating microseismic events and reconstructing the velocity model simultaneously in real-time from seismic waveforms. Tanaka et al [49] employed a deep learning model to perform moment tensor inversion of acoustic emissions during a hydraulic fracturing experiment of granite rock and obtained 54,727 solutions.…”
Section: Deep Learningmentioning
confidence: 99%
“…Polarity analysis of P-wave first motions (Bennour et al 2015;Stoeckhert et al 2015) and moment tensor (MT) analysis (Rodriguez et al 2017;Yamamoto et al 2019;Naoi et al 2020) of such AE events have provided information on the fracture modes of individual AEs, which have been helpful to understand the progression of macroscopic fractures. Tanaka et al (2021) have revealed a detailed preparation process of hydraulic fracturing from many MT solutions (54 727 for 10 experiments) that were obtained by introducing a deep learning technique.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the sensitivity should be estimated for each transducer after its installation. Some studies (Yamamoto et al 2019;Naoi et al 2020;Tanaka et al 2021) have overcome this problem by estimating the relative sensitivity of each transducer using data from pulse radiation tests that were conducted immediately before each experiment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations